Advancing Ambulance Services For Optimal Emergency Response: A Comprehensive Review Of Global Practices And Innovations (The Review of Diabetic Studies, 2025)
Ambulance services form the backbone of prehospital emergency care, providing critical interventions that often determine patient survival and long-term outcomes. This comprehensive review explores global practices, innovations, and strategies aimed at advancing ambulance service performance for optimal emergency response. Using systematic literature from 2016 to 2025, this study synthesizes findings on operational models, workforce development, digital technologies, and system integration frameworks implemented across diverse healthcare contexts. The review highlights key innovations such as AI-assisted dispatch systems, telemedicine-supported ambulances, GPS-driven route optimization, and specialized mobile care units. Comparative analyses reveal that high-performing ambulance systems share core attributes: data-driven decision-making, continuous professional training, and collaboration between emergency departments and community networks. The findings underscore the importance of evidence-based policy frameworks and investment in digital infrastructure to improve response times, patient safety, and care quality. The review concludes with strategic recommendations to guide healthcare policymakers, emergency medical services (EMS) administrators, and researchers in designing resilient, efficient, and patient-centered ambulance systems globally.